1999
DOI: 10.1084/jem.189.12.1953
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesvirus 6 (HHV-6) Causes Severe Thymocyte Depletion in SCID-hu Thy/Liv Mice

Abstract: Human herpesvirus 6 (HHV-6) is a potentially immunosuppressive agent that may act as a cofactor in the progression of AIDS. Here, we describe the first small animal model of HHV-6 infection. HHV-6 subgroup A, strain GS, efficiently infected the human thymic tissue implanted in SCID-hu Thy/Liv mice, leading to the destruction of the graft. Viral DNA was detected in Thy/Liv implants by quantitative polymerase chain reaction (PCR) as early as 4 d after inoculation and peaked at day 14. The productive nature of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
46
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 33 publications
3
46
1
Order By: Relevance
“…As a result of several in vitro analyses, HHV-6 has been demonstrated to have immunomodulatory effects such as impaired T cell activation, decreased cytokine synthesis, and impaired dendritic cell functions. [37][38][39][40] Although several investigators have suggested that HHV-6 infection is positively associated with CMV disease 15,17,18 and fungal infection 7 in liver transplant recipients, a definitive association between HHV-6 infection and these opportunistic infections remains unclear. This study showed no association between HHV-6 reactivation and CMV antigenemia or fungal infection.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of several in vitro analyses, HHV-6 has been demonstrated to have immunomodulatory effects such as impaired T cell activation, decreased cytokine synthesis, and impaired dendritic cell functions. [37][38][39][40] Although several investigators have suggested that HHV-6 infection is positively associated with CMV disease 15,17,18 and fungal infection 7 in liver transplant recipients, a definitive association between HHV-6 infection and these opportunistic infections remains unclear. This study showed no association between HHV-6 reactivation and CMV antigenemia or fungal infection.…”
Section: Discussionmentioning
confidence: 99%
“…Models of HHV-6A and HHV-6B infection have been developed in marmosets and transgenic mice (46,47,54,55). Additionally, identification of naturally occurring herpesviruses related to human roseoloviruses has been reported by various groups, notably in pig-tailed macaques (56,57).…”
Section: Discussionmentioning
confidence: 99%
“…While we have not studied direct infection of T cells in vitro, our data strongly suggest that MRV has similar T-cell tropism. Furthermore, infection of humanized mice with HHV-6A showed severe loss of human CD4 ϩ cells in the thymus (45)(46)(47), and ex vivo infection of human lymphoid tissues decreased the CD4 ϩ T-cell number (48). The tissue tropism of human roseoloviruses may be very broad, involving a diverse array of organs and cell types (1).…”
Section: Discussionmentioning
confidence: 99%
“…Besides this role as an opportunistic agent, however, several lines of clinical and experimental evidence support the concept that HHV-6 may also act as an immunosuppressive agent in its own right. Both HHV-6 subgroups were shown to induce severe thymocyte depletion in heterochimeric SCID-hu thy/liv mice, with a predominant tropism and cytopathicity for immature thymic precursor cells (8). Disseminated coinfection with HHV-6A and -6B was linked to progressive and ultimately fatal immunodeficiency in a human immunodeficiency virus (HIV)-negative child (13).…”
mentioning
confidence: 99%